Aspect, communicative appeal, and temporal meaning in Biblical Hebrew verbal forms - Bergström, Ulf, 1974- (Linguistic studies in ancient West Semitic ;, 2022)
"Offers a new explanation for the expression of tense and aspect in Biblical Hebrew, demonstrating that the verbal forms have basic aspectual and derived temporal meanings"--